Stereoselection in the diels-alderase ribozyme: A molecular dynamics study - Berezniak, Tomasz; Jaeschke, Andres; Smith, Jeremy C.; Imhof, Petra (Journal of Computational Chemistry, 2012)
The Diels-Alderase ribozyme is an in vitro-evolved ribonucleic acid enzyme that catalyzes a [4 + 2] cycloaddition reaction between an anthracene diene and a maleimide dienophile. The ribozyme can in principle be used to selectively synthesize only one product enantiomer, depending on which of the two entrances to the catalytic pocket, "front" or "back", the substrate is permitted to use. Here, we investigate stereoselection and substrate recognition in the ribozyme by means of multiple molecular dynamics simulations, performed on each of the two substrates individually in the pocket, on the reactant state, and on the product state. The results are consistent with a binding mechanism in which the maleimide likely binds first followed by the anthracene, which enters preferentially through the front door. The free energy profiles for anthracene binding indicate that the pre-(R,R)-enantiomer conformation is slightly preferred, in agreement with the experimentally observed small enantiomeric excess of the (R,R)-enantiomer of the product. The reactant state is stabilized by the simultaneous presence of both substrates bound to their binding sites in the hydrophobic pocket as well as by stacking interactions between them. © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2020-02-18
Keywords: binding mechanism; enzyme catalysis; molecular dynamics; RNA; stereoselection